2004
DOI: 10.1152/ajpcell.00356.2003
|View full text |Cite
|
Sign up to set email alerts
|

Description of glucose transport in isolated bovine mammary epithelial cells by a three-compartment model

Abstract: Initial rates of glucose entry into isolated bovine mammary epithelial cells display moderate degrees of asymmetry and cooperative interactions between export and import sites. The present study examined the hypothesis that these kinetic features are due to compartmentalization of intracellular glucose. Net uptake of 3-O-methyl-d-[1-(3)H]glucose (3-OMG) by isolated bovine mammary epithelial cells was measured at 37 degrees C. The time course of 3-OMG net uptake was better fitted by a double-exponential equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Although the exact mechanism of GLUT1 function remains to be elucidated, it is clear from the time course of uptake by erythrocytes that the transporter translocates extracellular sugar across the plasma membrane into an intracellular compartment from which the sugar may diffuse into the bulk cytosol or, with a greater likelihood, escape back to the extracellular space (12,16). The same behavior was observed in bovine mammary epithelial cells in vitro (25) and is now apparent from in vivo mammary dilution curves.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Although the exact mechanism of GLUT1 function remains to be elucidated, it is clear from the time course of uptake by erythrocytes that the transporter translocates extracellular sugar across the plasma membrane into an intracellular compartment from which the sugar may diffuse into the bulk cytosol or, with a greater likelihood, escape back to the extracellular space (12,16). The same behavior was observed in bovine mammary epithelial cells in vitro (25) and is now apparent from in vivo mammary dilution curves.…”
Section: Discussionsupporting
confidence: 78%
“…The estimated r v for glucose of 0.34 is thus only 17% of the expected ratio and likely represents the size of the intermediate occlusion compartment. Occlusion volume was estimated at 30 -40% of intracellular glucose space in human erythrocytes (6,12) and 35% in cultured bovine mammary epithelial cells (25). Intracellular ATP will influence the size of the occlusion space, possibly through allosteric interaction with the GLUT1 homotetramer.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose transport into the epithelial cells of the mammary gland is specific, saturable, Na + -independent, and GLUCOSE TRANSPORTERS IN BOVINE MAMMARY GLAND E81 inhibitable by cytochalasin-B or phloretin in the guinea pig, rat, mouse, and cow (Amato and Loizzi, 1979;Threadgold et al, 1982;Prosser, 1988;Delaquis et al, 1993;Xiao and Cant, 2003;Xiao et al, 2004). For uptake of 3-O-methy-D-glucose in bovine mammary epithelial cells, the K m is 8.29 mM and the V max is 18.2 nmol/min per mg of protein (Xiao and Cant, 2003).…”
Section: Glucose Transport and Glucose Transporters In The Mammary Glandmentioning
confidence: 99%
“…However, the intracellular concentration of glucose influences the apparent K m and V max of entry (Xiao and Cant, 2003), as shown for human erythrocytes (Wheeler and Whelan, 1988;Cloherty et al, 1996). It has been suggested that the effect of intracellular glucose is an artifact of its compartmentalization (Carruthers, 1991;Naftalin and Rist, 1991;Xiao et al, 2004). A compartmental model of symmetric, carrier-mediated translocation of glucose across the plasma membrane into an occlusion space that also exchanges by diffusion with the bulk cytosol can reproduce the anomalous kinetic behavior of initial entry rates in human erythrocytes (Heard et al, 2000) and bovine mammary epithelial cells (Xiao et al, 2004).…”
Section: Introductionmentioning
confidence: 97%